Radical Scavenging and Cellular Antioxidant Activity of the Cocoa Shell Phenolic Compounds after Simulated Digestion - Silvia Cañas; Miguel Rebollo-Hernanz; Patricia Bermúdez-Gómez; Pilar Rodríguez-Rodríguez; Cheyenne Braojos; Alicia Gil-Ramírez; Vanesa Benítez; Yolanda Aguilera; María A. Martín-Cabrejas (MDPI AG, 2023)
The cocoa industry generates a considerable quantity of cocoa shell, a by-product with high levels of methylxanthines and phenolic compounds. Nevertheless, the digestion process can extensively modify these compounds' bioaccessibility, bioavailability, and bioactivity as a consequence of their transformation. Hence, this work's objective was to assess the influence of simulated gastrointestinal digestion on the concentration of phenolic compounds found in the cocoa shell flour (CSF) and the cocoa shell extract (CSE), as well as to investigate their radical scavenging capacity and antioxidant activity in both intestinal epithelial (IEC-6) and hepatic (HepG2) cells. The CSF and the CSE exhibited a high amount of methylxanthines (theobromine and caffeine) and phenolic compounds, mainly gallic acid and (+)-catechin, which persisted through the course of the simulated digestion. Gastrointestinal digestion increased the antioxidant capacity of the CSF and the CSE, which also displayed free radical scavenging capacity during the simulated digestion. Neither the CSF nor the CSE exhibited cytotoxicity in intestinal epithelial (IEC-6) or hepatic (HepG2) cells. Moreover, they effectively counteracted oxidative stress triggered by tert-butyl hydroperoxide (t-BHP) while preventing the decline of glutathione, thiol groups, superoxide dismutase, and catalase activities in both cell lines. Our study suggests that the cocoa shell may serve as a functional food ingredient for promoting health, owing to its rich concentration of antioxidant compounds that could support combating the cellular oxidative stress associated with chronic disease development.